2019
DOI: 10.1002/pro.3618
|View full text |Cite
|
Sign up to set email alerts
|

Side chain electrostatic interactions and pH‐dependent expansion of the intrinsically disordered, highly acidic carboxyl‐terminus of γ‐tubulin

Abstract: Intramolecular electrostatic attraction and repulsion strongly influence the conformational sampling of intrinsically disordered proteins and domains (IDPs). In order to better understand this complex relationship, we have used nuclear magnetic resonance to measure side chain pKa values and pH‐dependent translational diffusion coefficients for the unstructured and highly acidic carboxyl‐terminus of γ‐tubulin (γ‐CT), providing insight into how the net charge of an IDP relates to overall expansion or collapse of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 75 publications
(149 reference statements)
0
4
0
Order By: Relevance
“…At the same time, IDPs are extremely sensitive to environmental conditions; an effect often disregarded in predictive approaches. Among the different parameters that may affect IDPs' properties, the solution pH has a significant impact, mainly due to the high prevalence of ionizable residues in these polypeptides [14,15,17,29]. In this work, we demonstrated that the effect of pH on the disordered nature of a protein sequence could be easily predicted by evaluating the changes in protein charge and hydrophobicity as a function of this parameter.…”
Section: Discussionmentioning
confidence: 83%
“…At the same time, IDPs are extremely sensitive to environmental conditions; an effect often disregarded in predictive approaches. Among the different parameters that may affect IDPs' properties, the solution pH has a significant impact, mainly due to the high prevalence of ionizable residues in these polypeptides [14,15,17,29]. In this work, we demonstrated that the effect of pH on the disordered nature of a protein sequence could be easily predicted by evaluating the changes in protein charge and hydrophobicity as a function of this parameter.…”
Section: Discussionmentioning
confidence: 83%
“…Charge regulation is likely to be negligible in the salt concentration range where we studied ProTα-H1 complex formation experimentally (see SI Appendix for details and SI Appendix , Fig. S4 ) ( 74 , 75 ) and is therefore inconsequential for the interpretation of theoretical thermodynamic estimates; however, the estimates of the single-chain dimensions are slightly affected at low salt concentrations (see SI Appendix for details and SI Appendix , Fig. S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…It involves the alternate adsorption of two different polymers onto substrates, resulting in the gradual formation of a nanofilm. LbL assembly can be driven by numerous interactions, including electrostatic interaction, , hydrogen bond, covalent bond, hydrophobic interaction, and biological interaction . Of these, electrostatic interaction stands out as the primary and most widely used driving force because of its easily adjustable parameters. So, polyelectrolytes (PEs) have become the first choice for LbL nanofilm fabrication. However, it was not until the 1990s that Decher and Hong fabricated multilayer films by consecutive adsorption of polyanions and polycations, a more versatile technique that relies on solutions of macromolecules and could thus be successfully extended to other materials. ,, The wide range of materials makes it possible for the fabricated PE nanofilms to be applied in many fields, like regulating the cell environment and surface modification for different functions.…”
Section: Introductionmentioning
confidence: 99%